What do parents expect from a genetic diagnosis of their child with intellectual disability? - Dikow, Nicola; Moog, Ute; Karch, Stephanie; Sander, Anja; Kilian, Samuel; Reuner, Gitta (Journal of applied research in intellectual disabilities, 2019)
BACKGROUND: Caring for a child with intellectual disability (ID) has been associated with increased social and psychological burdens. Diagnostic and prognostic uncertainty may enhance emotional stress in families. - METHOD: The present authors assessed the motivations, expectations, mental health, physical health and the quality of life of 194 parents whose children with intellectual disability were undergoing a genetic diagnostic workup. - RESULTS: Most parents considered a diagnosis highly relevant for their own emotional relief, their child's therapies and education, or family planning. Parental mental health was significantly lower compared with the normative sample, but physical health was not different. The severity of the child's intellectual disability correlated negatively with their parents' mental and physical health, quality of life, and positively with parental anxiety. - CONCLUSION: Healthcare providers should be aware of the disadvantages facing families with intellectually disabled children. Receiving practical, social and psychological support as well as genetic testing might be particularly relevant for families with severely disabled children.
Gesehen am 06.05.2019